Schreiben im Zwiegespräch / Writing as Dialogue Praktiken des Mentorats und Lektorats in der zeitgenössischen Literatur / Practices of editors and mentors in contemporary literature - Mohs , Johanne; Zimmermann, Katrin; Caffari, Marie (Lettre, 2019)
''Although practices of editing and mentoring are part of an author's daily activities, they have previously been largely neglected by the literary studies. The bilingual volume therefore assembles players from the fields of literary production and theories of authorship and the writing process, who discuss the development towards an opening up of the creative writing process. Their contributions encompass not only reports of experiences made by authors, editors, and mentors and insights into teaching methods applied in creative writing classes at higher education institutions in different European countries. They also explore theoretical approaches to an intersubjective literary practice as well as suggestions for the definition of a dialogic notion of literature in the age of online publishing.